Enhancing Teamwork Behavior and Academic Performance through Cooperative Learning Utilizing Team Games Tournamentfor Sixth Grade Students - บุญมี วรารัตน์; คุ้นเคย อรุณรุ่ง; อินทรางกูร ณ อยุธยา ปฐมพรณ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The objectives of this research were to: 1) examine the collaborative behavior of Grade 6 students in cooperative learning through Team Games Tournament, and 2) evaluate the academic performance in Unit 1, Work Management Skills, of the Career Education subject among Grade 6 students before and after participating in cooperative learning with Team Games Tournament. The sample group consisted of 38 students from Grade 6/1 at Baan Suan Luang School, chosen via cluster sampling. The research instruments comprised: 1) lesson plans for cooperative learning utilizing Team Games Tournament, 2) an academic success assessment, and 3) a teamwork behavior evaluation form. The statistical methods employed for data analysis included the mean, standard deviation, and t-test for dependent samples. The research findings revealed that: 1) students engaged in cooperative learning through Team Games Tournament utilizing games exhibited overall post-learning teamwork behavior scores at a commendable level, surpassing the pre-learning scores, which were at a satisfactory level; and 2) students participating in cooperative learning via Team Games Tournament with games demonstrated post-learning academic achievement scores significantly elevated compared to pre-learning scores at the .01 level.